Effect of Different Powers of Er,Cr:YSGG Laser Treatment on Surface Morphology of Microhybride Composite Resin: Scanning Electron Microscope (SEM) Evaluation - Mirzaei, Mansore; Yasini, Esmaeil; Tavakoli, Atefeh; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2015)
Introduction: The aim of this study was to evaluate and compare microhybride composite treated by bur and different power of Erbium, Chromium doped Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) laser by Scanning Electron Microscope (SEM). Methods: 21 microhybride composite blocks (DiaFil TM, DiaDent, Korea) with 2 × 4 × 4 mm dimensions were made. The bonding surface of these blocks were polished, The samples were put into 6 groups for laser irradiation as follows: Group 1 (power: 1W, Energy: 50 mJ); Group 2(power: 2 W, Energy: 100mJ); Group 3 (power: 3W, Energy: 150mJ); Group 4 (power: 4W, Energy: 200mJ); Group 5 (power: 5W, Energy: 250mJ) and Group 6(power:6 W, Energy :300mJ). One group prepared by bur- treated. All samples were prepared by repetition rate of 20 Hz. Then, the samples were prepared for SEM examination. Result: Some irregularities were seen in Er,Cr:YSGG laser samples in comparison to Bur group that produced favorable surface for adhesion of repair composite. Conclusion: Among different lasers, Er;Cr:YSGG laser can be chosen as a suitable technique for surface treatment of unsatisfactory composites. Key words: SEM evalution; laser; composite resin